Internationalisation and quality assurance. - van Gaalen, Adinda, ....- (Amsterdam : EAIE (European Association for International Education), 2010)
Quality assurance is rapidly taking on a vital role when it comes to managing the increasingly complex internationalisation process. Not only is it essential in reaching institutional goals in a controlled manner, it is also becoming an integral part of maintaining and improving every institution's reputation. Although quality assurance is a relatively new phenomenon, it is something we can no longer do without. This publication provides basic facts every international educator needs to know regarding the quality assurance of internationalisation. It will help you implement and monitor the quality of internationalisation at your institution.
Keywords: Internationalisering -- Hoger onderwijs; Kwaliteitszorg -- Hoger onderwijs